Marketing Communication Strategy Via Instagram In Increasing Brand Awareness Dailysocial.id - Ardian Utomo; Shavira Diah Putri; Bambang Sujarwadi; Widhihatmini; Arum Marwati (Jurnal Komunikasi dan Kajian Media, 2024)
Technological developments in the digital era mean that media must be able to keep up with the times by switching to social media platforms. Companies must use appropriate marketing communication strategies to survive and compete with their competitors. This research aims to determine marketing communication strategies via Instagram to increase DailySocial.id brand awareness. It used qualitative research methods with a Marketing Communication Mix theory approach, including advertising, personal selling, interactive marketing, public relations and publicity, direct marketing, events and experience, and sales promotion. The data collection techniques used were observation, interviews, and documentation. The research results show that the marketing communication strategy carried out by implementing a marketing communication mix via Instagram can increase DailySocial.id brand awareness because users can find information through uploaded content, get education about what the company offers, and interact with the Instagram account profile @dailysocial.id becomes a medium for interaction between users and companies, public relations, and publicity, namely carrying out two-way communication and sales promotion by bringing in new audiences and more participants getting involved, making more people aware of the brand. This is also proven by the results of brand impressions and social media engagement, which have also increased.